Nos "bosques" da saudade: um estudo historiográfico - Pereira, Maria Clara Costa (2019)
In this dissertation I seek to understand, through the interpretation of documents published in the newspaper A Tribuna (1919-1942) of Uberabinha/Uberlândia, the discursive constructions that constitute different representations and images of saudade and the saudade’s being. The narrative around the saudade enunciates it with senses and meanings sometimes close and sometimes distant, in a process that authorizes to think such word as territory of political struggle. Its articulation with other conceptual constructs, like those of city, crisis and myth, is potentialized as an instrument for structuring this history. Ground my arguments the theoretical considerations regarding the approximations between history and literature, the memory’s belongings, the desires towards and in the urban space, the fabrications of reality and its projects, the dialogues between social structures and sensibilities, and the link between artistic productions and the word’s meanings and configurations. I understand the word saudade as key to entry in a discursive order, which of I also participate. Its (in)definitions express desires of truth, perspectives and projections through texture between invented pasts, presents and futures that situate the subject in his permanent poetic walks and adventures in the life’s woods.